INFLUENCE OF CARDANOL ENCAPSULATED ON THE PROPERTIES OF POLY(LACTIC ACID) MICROPARTICLES - Cardoso,Jaciene J. F. (2018)
In this study, microparticles of poly(lactic acid) (PLA) were produced to encapsulate cardanol, varying molar mass of the polymer matrix, concentration of the emulsifier (PVA) and concentration of the chemical additive (cardanol). The droplet size distribution, polydispersity index, morphology, the interaction between cardanol and PLA, cardanol encapsulation efficiency and release profile of this chemical additive were assessed. The morphological characterization showed that the microparticles containing cardanol were presented as microcapsules up to a maximum cardanol concentration limit that could be incorporated. The addition of cardanol during the production of the microparticles led to an increase in the average diameter of the microparticles obtained, both those with low and high molar mass (MPLA3 and MPLA100, respectively), with the increase depending on the quantity of cardanol incorporated. DSC results showed a shift in melting point and a change in Tg and Tm with the incorporation of cardanol, suggesting an interaction between cardanol and PLA matrix. Higher encapsulation efficiency and slower release of cardanol were achieved when using microparticles with higher molar mass (MPLA100). The microparticles of MPLA100/1PVA/50C provided the slowest additive release among the formulations tested. Therefore, the processes for encapsulation and controlled release of cardanol in the PLA matrix were efficient.